Rab7 inhibitor enhances stem cell differentiation into keratinocyte-like cells with anti-inflammatory properties - Alghazali, Raghad; Tabebi, Mouna; Elmasry, Moustafa; El-Serafi, Ahmed (Frontiers in Immunology, 2025)
Management of difficult-to-heal skin wounds presents a significant clinical challenge, particularly when associated with inflammatory skin disorders. The differentiation of stem cells into keratinocyte-like cells has been explored as a potential regenerative therapy. Ras-related protein (Rab) 7, a key regulator of membrane trafficking, influences the activity of several growth factors. In this study, the competitive Rab7 inhibitor, CID-1067700, was investigated for the differentiation of adipose-derived stem cell into keratinocyte-like cells. This treatment upregulated several epidermal markers, including P63, cytokeratin 5 and 14 and filaggrin, while downregulated the stem cell marker, vimentin. Microarray data showed upregulation of the anti-inflammatory gene HMOX-1, coupled with the downregulation of various inflammation-related pathways, such as TNF, chemokine, AGE-RAGE and IL-17 signalling cascades, as well as cytokine-cytokine receptor interaction pathways. Gene set enrichment analysis predicted Ehmt2, an epigenetic regulator, to be the top activated upstream regulator, enhancing the transcriptional activity. Protein array analysis showed reduced secretion of several inflammatory cytokines, including IL-1α, IL-8, IL-17A, and IL-32, while enhancing the secretion of the epidermal growth factor. Our findings provide preliminary evidence that CID-1067700, as an additive to the differentiation media, not only enhances stem cell differentiation into keratinocyte-like cells, but also improves their anti-inflammatory properties. These combined regenerative and anti-inflammatory properties may offer significant therapeutic potential for patients with chronic skin wounds, particularly those with underlying inflammatory conditions.